키예프－제2 예루살렘설의 기원과 전개 - 鄭英珠; Jung Youngjoo (중소연구, 2019)
키예프는 동슬라브인이 정교를 처음 도입한 도시이기 때문에 그 의미가 각별하다. 11세기부터 키예프의 성직자들은 키예프를 기독교 성지와 연관시키며 키예프의 역할과 사명을 강조했다. 다만 키예프에 신성을 부여하는 초기에 루스인들에게 있어 키예프는 콘스탄티노플의, 콘스탄티노플은 예루살렘의 변주였다. 본고에서는 우선 키예프－제2 예루살렘설의 자세한 내용과 형성과정을 살펴본다. 다음으로 키예프 루스인들이 키예프에 예루살렘을 어떠한 방식으로 재현하며 연관성과 계승권을 주장하게 되었는지 조망한다. 이어서 모스크바－제3 로마설과의 연관성을 짚어보고, 키예프－제2 예루살렘설에서 시작한 루스인들의 메시아주의가 모스크바－제3 로마설로 이어지는 과정을 살펴본다. 끝으로 키예프－제2 예루살렘설이 근 현대 우크라이나와 러시아 사회에서 재조명되는 양상을 살펴본다. Kyiv, Ukraine carries a special meaning because it is the city where Eastern Slavs adopted Orthodox Christianity for the first time. Since the 11th century, clerics of Kyiv associated the city as a sacred place for Christianity and emphasized the roles and missions of Kyiv. However, in the beginning of divinizing Kyiv, the city was a variation of Constantinople which was also a variation of Jerusalem for the people of Rus. This paper first examines the details and formation of the concept of “Kyiv as the second Jerusalem” and sheds light on how the people of Kyivan Rus recreated Jerusalem in the city, claiming the association and their succession rights of Kyiv. Next, this research discusses its correlation with the “Moscow as the third Rome” Concept and the process how the Messianism by Rus people, which started from the concept of “Kyiv as the second Jerusalem”, leads to the concept of “Moscow as the third Rome”. Finally, this paper analyzes how the concept of “Kyiv as the second Jerusalem” is shed new light on in modern and contemporary societies of Russia and Ukraine.